Contribution to the study of blastomycosis (Conclusion) - Lozada Benavente, Samuel (1920)
Although blastomycosis producer agent is known, do not know how to enter the body and if it does by some intermediate vector. Undoubtedly transmitted disease that requires a middleman, it is not contagious despite being microbial. We have learned to deal with this kind of patients, who despite having very advanced external injuries, living with a wife and children, away from where they had acquired the disease, such as the city of La Paz, no cases were observed contagion; Moreover, there are patients who have lived in the Lazaretto of La Paz, 11 and 12, without regard to the most elementary principles of hygiene, while in many instances have caught eating from the same plate, with individuals of other diseases, without having seen or heard of a single case of infection. Always when interrogating these patients state that the primary lesion (chancre blastomicósico) appeared on the exposed parts, and then, after some time, outsource the secondary lesions.